Method of using amorphous refractory
By blending controlled amounts of alumina cement with calcium and strontium aluminate, the refractories exhibit enhanced structural and heat spalling resistance, addressing the durability issues of existing monolithic refractories under high-temperature conditions.
Patent Information
- Application Number
- JP2024067394
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-04-18
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2044-04-18
AI Technical Summary
Existing monolithic refractories suffer from insufficient structural spalling resistance and heat spalling resistance due to inadequate consideration of fracture energy and hot mechanical properties, particularly when exposed to high temperatures and slag infiltration.
Incorporating specific amounts of alumina cement containing calcium aluminate and strontium aluminate into refractory raw materials, with controlled proportions to enhance fracture energy and spalling resistance, including formulations with 7-20% by mass of alumina cement and 10-40% by mass of strontium aluminate.
The method significantly improves the durability and resistance of monolithic refractories to structural and heat spalling, reducing unit consumption, construction frequency, and environmental impact while maintaining high fracture energy and strength at elevated temperatures.
Smart Images

Figure 2025009824000001 
Figure 2025009824000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for using a monolithic refractory that is required to have high durability in hot working.In this specification, "x to y" expressing a range of numerical values means not less than x and not more than y, and includes the boundary value. [Background technology]
[0002] The refractories mainly used in steelworks are being converted from shaped refractories such as bricks to monolithic refractories due to the decrease in furnace builders. In particular, the steel bath part that comes into contact with the molten steel in the ladle has been converted to monolithic refractories early, and is now being used in many factories. The main component of the material is alumina, and alumina-magnesia and alumina-spinel refractories, which are blended with magnesia and spinel, are commonly used.
[0003] In general, refractories are vulnerable to sudden changes in temperature, especially when shrinkage occurs due to cooling. For example, in shaped refractories, the numerous joints open up little by little to absorb dimensional changes, so the refractory hardly suffers any damage. On the other hand, since unshaped refractories do not have joints, the refractory as a whole must absorb dimensional changes, and when the dimensional changes are particularly large, they often suffer from thermal spalling damage, which causes cracks perpendicular to the working surface.
[0004] In addition, when the ladle is receiving steel and casting, as slag moves while in contact with the refractory surface in the steel bath, the slag often penetrates into the refractory and forms an infiltration layer. The resulting infiltration layer has a higher density and elastic modulus than the original refractory, and is susceptible to cracking and damage due to structural spalling parallel to the working surface caused by differences in physical properties such as thermal expansion coefficient compared to the original refractory, leading to a decrease in durability. In particular, the infiltration layer is susceptible to cracking as mentioned above, and the combined factors of cracks due to structural spalling cause partial peeling of the refractory and its progression, furthering the damage.
[0005] One of the factors of slag infiltration is the effect of calcium oxide, which easily forms low-melting compounds with slag components. Calcium oxide is a component contained as calcium aluminate in alumina cement, which is commonly used in monolithic refractories. Refractories are required to have a short construction, i.e., non-operational period, and are required to develop strength so that they can be removed from the form, generally the next day or 24 hours after pouring. For this reason, alumina cement, which develops curing strength faster than Portland cement, is used. Calcium oxide in alumina cement reacts with slag at high temperatures to form low-melting compounds and produce a liquid phase. This reduces the structural strength of monolithic refractories at high temperatures, making the above-mentioned structural spalling cracks more likely to occur.
[0006] In order to suppress the effects of slag due to the presence of calcium oxide, improvements have been made in the direction of reducing the amount of cement, such as low-cement and extremely low-cement castables. Further studies on reducing the amount of cement have been conducted, and for example, Patent Document 1 proposes a refractory material that uses alumina sol and does not use alumina cement. It is characterized by the absence of calcium oxide, and is said to be possible to apply by pouring, to have no problems with curing strength and explosion resistance, and to have excellent heat spalling resistance.
[0007] Alumina cement that does not contain calcium oxide is also being studied. For example, Patent Document 2 proposes a cement that uses strontium aluminate instead of calcium aluminate, and a refractory that uses 0.2 volume % or more and less than 20 volume % of the cement. Patent Document 3 similarly proposes a refractory that uses 0.5 volume % or more and 10 volume % or less of cement that uses strontium aluminate. Since the cement that uses strontium aluminate does not contain calcium oxide or contains only a small amount of calcium oxide, it is considered to have poor reactivity with slag and hardly generates an infiltration layer. Refractories that contain these strontium aluminate-containing cements have been studied for their corrosion resistance against slag at high temperatures as well as their strength after curing. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2020-203807 A [Patent Document 2] JP2010-120843 Public Relations [Patent Document 3] JP2017-066025 Public Relations Summary of the Invention [Problem to be solved by the invention]
[0009] However, the above-mentioned conventional techniques have the following problems. That is, the technology described in Patent Document 1 does not consider fracture energy, and is insufficient from the viewpoint of suppressing damage during hot working. The technology described in Patent Document 2 does not consider hot mechanical properties of the monolithic refractory. The technology described in Patent Document 3 only considers improvement of heat spalling resistance with respect to hot mechanical properties, and does not consider the most important fracture energy, and is insufficient from the viewpoint of suppressing damage during hot working.
[0010] The present invention has been made in view of the above, and aims to propose a method of using a monolithic refractory having excellent resistance to structural spalling and heat spalling by focusing on hot fracture energy. [Means for solving the problem]
[0011] The first method of using the monolithic refractory according to the present invention, which advantageously solves the above problems, is characterized in that the monolithic refractory is used in an environment in which it comes into contact with a molten material at 1000° C. or higher, and the refractory raw materials contain 7% by mass or less of alumina cement containing 10-40% by mass of CaO as calcium aluminate and 2% by mass or more of alumina cement containing 10-40% by mass of SrO as strontium aluminate, in a total amount of 7% by mass or more and less than 20% by mass. Note that the first method of using the monolithic refractory according to the present invention is more preferably solved by using a monolithic refractory containing 10% by mass or more of alumina cement containing 10-40% by mass of SrO as strontium aluminate.
[0012] The second method of using the monolithic refractory of the present invention, which advantageously solves the above-mentioned problems, is characterized in that the monolithic refractory is used in an environment in which it comes into contact with a molten material at 1000°C or higher, in which alumina cement containing 10 to 40 mass% SrO as strontium aluminate is mixed in the refractory raw materials without mixing any alumina cement containing calcium aluminate, and in which the alumina cement is mixed in an amount of 5 mass% or more but less than 20 mass%.
[0013] The third method of using the monolithic refractory according to the present invention, which advantageously solves the above problems, is characterized in that the monolithic refractory is used in an environment in which it comes into contact with a molten material at 800° C. or higher, and the refractory raw materials contain 7 mass% or less of alumina cement containing 10 to 40 mass% of CaO as calcium aluminate and 7 mass% or more of alumina cement containing 10 to 40 mass% of SrO as strontium aluminate, and less than 20 mass% in total. Note that the third method of using the monolithic refractory according to the present invention is more preferably solved by using a monolithic refractory containing 10 mass% or more of alumina cement containing 10 to 40 mass% of SrO as strontium aluminate.
[0014] The method for using any one of the above-mentioned monolithic refractories according to the present invention is as follows: (a) the temperature of the melt is 1200° C. or higher; (b) the temperature of the melt is 1400° C. or higher; (c) The refractory raw materials, excluding cement, are mainly composed of alumina and contain magnesia; (d) the molten metal includes molten pig iron or molten steel, and the castable refractory is applied to a steelmaking vessel; This may be a more preferable solution. Effect of the Invention
[0015] According to the method for using the monolithic refractory of the present invention, an appropriate amount of alumina cement containing strontium aluminate is mixed. Furthermore, the amount of alumina cement containing calcium aluminate is limited or not mixed. This significantly improves the hot fracture energy of the refractory, and a highly durable monolithic refractory having both high structural spalling resistance and heat spalling resistance can be obtained. This leads to a reduction in the unit use of the refractory, as well as a reduction in the work load due to a reduction in the frequency of construction, and a reduction in the costs of each. Furthermore, the frequency of demolition is reduced, which leads to a reduction in the cost of dismantling debris and the environmental load. In addition, the reduction in the unit use of the refractory also reduces the environmental load associated with the production of raw materials. In this way, in addition to the economic effect, the reduction in the work load and the load on the natural environment can be enjoyed, making it industrially useful. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the embodiments of the present invention will be described in detail. Note that the following embodiments are merely examples of compositions and methods for embodying the technical idea of the present invention, and are not intended to limit the configuration to the following. In other words, the technical idea of the present invention can be modified in various ways within the technical scope described in the claims.
[0017] In the method of using the monolithic refractory according to the present embodiment, a part of the alumina cement containing calcium aluminate is replaced with alumina cement containing strontium aluminate instead of calcium aluminate. The monolithic refractory according to the present embodiment is used in an environment where it comes into contact with a high-temperature molten material of 1000°C or more. In this case, the alumina cement containing calcium aluminate is mixed in an amount of 7% or less and less than 20% in total, based on the mass of the refractory raw material having a particle size of 8 mm or less.
[0018] Conventional alumina cement contains 10 to 40 mass% of CaO. CaO is contained in cement as calcium aluminate, for example, in compositions such as 3CaO·Al2O3, CaO·Al2O3, and 12CaO·7Al2O3. Alumina cement containing strontium aluminate is obtained by replacing the above CaO with SrO, and the content of CaO is 3 mass% or less. In a blend containing alumina cement containing calcium aluminate in excess of the upper limit, the CaO content in the monolithic refractory is too high, so that the infiltration of slag progresses and the fracture energy in a high temperature range of 1000°C or higher decreases. As a result, the structural spalling resistance and heat spalling resistance deteriorate. If the blending amount of alumina cement containing strontium aluminate is less than the lower limit, the effect of replacing calcium aluminate is too small. As a result, the effect of improving structural spalling resistance and heat spalling resistance cannot be expected. Preferably, the alumina cement containing calcium aluminate is blended at 2 mass% or less, and the alumina cement containing strontium aluminate is blended at 5 mass% or more. More preferably, the alumina cement containing calcium aluminate is not blended. When the alumina cement containing calcium aluminate is not blended, blending 5 mass% or more of the alumina cement containing strontium aluminate in the monolithic refractory allows the monolithic refractory to be used in an environment in contact with a high-temperature melt of 1000°C or more. However, blending 10 mass% or more of the alumina cement containing strontium aluminate can suppress a decrease in fracture energy in a high-temperature range of 1000°C or more, even if the alumina cement containing calcium aluminate is blended in the range of 7 mass% or less.
[0019] Secondly, by blending 7% by mass or more of alumina cement containing strontium aluminate in the monolithic refractory and 7% by mass or less of alumina cement containing calcium aluminate, the hot strength of this monolithic refractory is improved compared to conventional materials when used in an environment in which it comes into contact with a high-temperature molten material of 800° C. or more. Furthermore, by blending 10% by mass or more of alumina cement containing strontium aluminate, a decrease in fracture energy in the high-temperature range of 800° C. or more can be suppressed even if the alumina cement containing calcium aluminate is blended in the range of 7% by mass or less.
[0020] If the total amount of alumina cement is less than the lower limit, the bending strength is low and the material is not suitable for use as a monolithic refractory. If the total amount of alumina cement is more than the upper limit, the pot life becomes too short and the material is not suitable for use as a monolithic refractory for on-site construction.
[0021] The fracture energy at 1000°C is preferably 0.64 N / mm or more, more preferably 0.70 N / mm or more, and even more preferably 0.85 N / mm or more. The fracture energy at 1200°C is preferably 0.52 N / mm or more, more preferably 0.65 N / mm or more, and even more preferably 0.85 N / mm or more. The fracture energy at 1400°C is preferably 0.12 N / mm or more, more preferably 0.23 N / mm or more, and even more preferably 0.30 N / mm or more. In addition, the hot strength at 800°C is preferably 21.0 MPa or more, and even more preferably 22.0 MPa or more. In addition, the infiltration index of the slag is preferably less than 100, more preferably 50 or less, and even more preferably 30 or less, with the conventional material being taken as 100.
[0022] Therefore, the monolithic refractory according to this embodiment has structural spalling resistance and heat spalling resistance when used in an environment where it comes into contact with a high-temperature melt at 800° C. or higher or 1000° C. or higher, is suitable for use in an environment where it comes into contact with a high-temperature melt at 1200° C. or higher, and is even more suitable for use in an environment where it comes into contact with a high-temperature melt at 1400° C. or higher.
[0023] In this embodiment, it is preferable that the refractory raw material other than the cement contains alumina as a main component and magnesia. Here, the main component means more than 50 mass%, and preferably 70 mass% or more. For example, it is an Al2O3-7 mass% MgO castable material. It can contain MgO in the range of 2 to 15 mass%.
[0024] The monolithic refractory according to the present embodiment can be widely applied to vessels and devices that handle molten pig iron tapped from a blast furnace, refined molten steel, and the like. Examples include molten pig iron ladles, molten steel ladles, vacuum degassing devices, and tundishes. For example, among existing monolithic refractories mainly composed of alumina, it is suitable for use as a replacement for parts where cracks due to structural spalling or heat spalling are a problem. In addition, in consideration of the reaction with slag, it may be applied to parts where a monolithic refractory is currently used. Although the high-temperature melt has been described using molten pig iron and molten steel as examples, it can also be applied to other high-temperature melts. EXAMPLES
[0025] The present invention will be described in detail below with reference to examples. The hot properties of monolithic refractories containing alumina cement containing strontium aluminate were investigated. [Test level] As a comparative example (No. 12), a monolithic refractory was used, which was composed of refractory raw materials with a maximum particle size of 8 mm or less and did not contain coarse aggregate, and contained 7% by mass of magnesia. Alumina cement containing 7% by mass of calcium aluminate was used for this monolithic refractory.
[0026] A base material was prepared from the monolithic refractory of Comparative Example No. 12 without alumina cement as Examples No. 1 to 11 and 13. As an alumina cement containing calcium aluminate (hereinafter simply referred to as alumina cement), commercially available high alumina cement H manufactured by Denka Co., Ltd. was prepared, and as an alumina cement containing strontium aluminate (hereinafter referred to as SrO cement), high alumina cement Super A09N manufactured by Denka Co., Ltd. was prepared.
[0027] The workability and hot properties were evaluated using the monolithic refractories with the composition shown in Tables 1 and 2. No. 12 is a conventional monolithic refractory containing no SrO cement and 7 mass% alumina cement. Nos. 1 and 2 are monolithic refractories in which part of the alumina cement of No. 12 is replaced with SrO cement. Nos. 3 and 4 are monolithic refractories containing no alumina cement and containing 5 mass% and 7 mass% SrO cement, respectively. Nos. 5 to 11 and 13 are monolithic refractories containing an increased amount of SrO cement than No. 4. Nos. 14 to 18 are monolithic refractories containing 10 mass% or more SrO cement and also containing alumina cement. The amount of water added during mixing was a constant amount of 6 mass% on the outer side of the total amount of refractory materials at all levels.
[0028] [Evaluation method] <Workability> Regarding workability, each level of monolithic refractory was mixed and then placed in a vinyl bag, and the tap flow value (mm) was measured immediately after mixing and every 0.5 hours according to the method specified in JIS R2521:1995. The tap flow value immediately after mixing and the pot life (Hr) are shown in Tables 1 and 2. The pot life (Hr) is defined as the time when the tap flow value becomes less than 130 mm. A pot life of 2 hours or more was used as an indicator of on-site workability.
[0029] <Hot properties> The hot properties were evaluated using slag infiltration, hot bending strength, hot fracture energy, and dynamic modulus ratio in spalling test, and the results are shown in Tables 1 and 2. Slag infiltration was evaluated by a rotating drum test. A synthetic slag was used, in which the ratio of calcium oxide and silicon dioxide components was 3:1, and the content of iron oxide in the slag converted to Fe (T.Fe) was 14 mass%. After mixing the 17 levels of mix materials except for No. 13, they were cast into a trapezoidal columnar mold, cured, dried, and then fired in air at 1650℃ for 3 hours to obtain 5 test pieces for each level. Each of the 12 test pieces was assembled into a cylindrical shape, heated to 1650℃, and synthetic slag was added. The slag was discharged and new slag was added every 30 minutes, and the test was performed for a total of 2 hours. The test was carried out five times, and after the test, the total thickness of the corrosion damage and the discoloration due to slag infiltration of each test piece was measured, and the average of the five measurements was calculated. The ratio of the average value of each level to the average value of the measurement value of No. 12 was evaluated using an index with No. 12 set to 100. The smaller the index, the better the resistance to slag infiltration.
[0030] The hot bending strength was measured in air at intervals of 200°C between 800°C and 1400°C, and the hot fracture energy was calculated from the load-displacement curve. After mixing the refractory raw materials of 17 levels except for No. 13, they were cast into a rectangular mold measuring 40mm x 40mm x 160mm and cured at room temperature at 20°C for 24 hours. After drying at 110°C for 24 hours, they were fired at 1650°C for 3 hours in air to obtain five test pieces for each level. The test pieces were set in a hot bending tester and heated to each temperature up to 1400°C, and then a three-point bending test was performed at a crosshead speed of 0.5mm / min and a support distance of 100mm. Furthermore, the hot fracture energy was calculated from the load-displacement curve of the test. Evaluations of both hot bending strength and hot fracture energy were performed by comparing the average values of five pieces for each level.
[0031] For the spalling test, the 17 levels of the composition except for No. 13 were mixed, then cast into a rectangular mold measuring 30mm x 30mm x 120mm, and cured at room temperature at 20℃ for 24 hours. After that, they were dried at 110℃ for 24 hours, and then sintered in air at 1650℃ for 3 hours to obtain five test pieces for each level. After the test pieces were made, the dynamic modulus of elasticity E0 was measured. After making the test pieces, they were placed in an electric furnace heated to 1400℃, held for 15 minutes, and then cooled in a room at 20℃. The dynamic modulus of elasticity was measured after the temperature had decreased to room temperature. This was repeated, and the ratio E3 / E0 of the dynamic modulus of elasticity E3 after the third test was completed was calculated. Five pieces of each level were tested, and the average value of each level was calculated and compared.
[0032] [Table 1]
[0033] [Table 2]
[0034] As a result of the workability evaluation, only the test piece No. 13, which had a SrO cement content of 20 mass%, had a tap flow value of 100 mm immediately after mixing, showing no fluidity at all. The tap flow values of the other levels exceeded the target lower limit of 130 mm. No. 13 had no fluidity and could not be cast normally, so a test piece for evaluating the hot properties could not be made.
[0035] The pot life evaluation results are explained below. As the SrO cement content increases, the pot life tends to become shorter. All levels exceeded the target of 2 hours except for No. 13, which showed no fluidity with a tap flow of 100 mm immediately after mixing. Therefore, No. 1 to 11 are suitable for on-site construction, just like conventional unshaped refractories.
[0036] The evaluation results of slag penetration are explained below. The results are greatly affected by the amount of normal alumina cement used, with a large difference between Nos. 1, 2 and 12, which use normal alumina cement, and the other levels (Nos. 3-11) which use SrO cement alone. The slag penetration index of monolithic refractories using only SrO cement was very small. However, in levels where the SrO cement amount was 10 mass% or more and normal alumina cement was used (Nos. 14-18), the same slag penetration index was obtained, even when compared with levels where only SrO cement was used (Nos. 8-10) which use the same total amount of SrO cement and normal alumina cement.
[0037] The results of hot bending strength are explained. For No. 12, high strength was observed at 800°C and 1000°C when the SrO cement content was 7% or more by mass. At 1200°C, high strength was observed when the SrO cement content was 2% or more by mass, and at 1400°C, high strength was observed when the SrO cement content was 5% or more by mass. In addition, at each temperature, when normal alumina cement was not used, the strength increased with the increase in the SrO cement content, and high strength was observed especially when the SrO cement content was 10% or more by mass. When the SrO cement content was 14% or more by mass, there was almost no change in strength or, conversely, it decreased. In the levels where the SrO cement content was 10% or more by mass and normal alumina cement was used (No. 14-18), the same hot bending strength was obtained compared to the levels where only SrO cement was used (No. 8-10) where the total amount of SrO cement and normal alumina cement was about the same.
[0038] The hot fracture energy calculated from the hot bending test results is explained below. At 800°C, the hot fracture energy gradually decreased up to an SrO cement content of 5 mass%, then started to increase. The rate of increase was high from 9 mass% to 12 mass% SrO cement content, and the value was higher than that of No. 12 at 10 mass% or more. In addition, at an SrO cement content of 11 mass% or more, the hot fracture energy remained almost the same or tended to decrease. At 1000°C to 1400°C, the hot fracture energy increased with an increase in the SrO cement content up to 14 mass%. At an SrO cement content of 14 mass% or more, the hot fracture energy remained almost the same or tended to decrease. The increasing trend of the hot fracture energy at an SrO cement content of 5 mass% or more was almost the same as that at 800°C. In the levels where the SrO cement content was 10 mass% or more and normal alumina cement was used (Nos. 14 to 18), the same hot fracture energy was obtained compared to the levels where only SrO cement was used (Nos. 8 to 10) where the total amount of SrO cement and normal alumina cement was approximately the same.
[0039] The results of the spalling test are as follows. For No. 12, No. 1, No. 2, and No. 4, the dynamic modulus ratio E3 / E0 increased almost linearly with the increase in the SrO cement content, with the total cement content being the same. For No. 5 to No. 7, the dynamic modulus ratio E3 / E0 increased sharply with the increase in the SrO cement content. The increase between No. 6 and No. 7 was the largest. For No. 7 to No. 10, the dynamic modulus ratio E3 / E0 was almost the same at SrO cement content of 11% to 17% by mass. For No. 11, the dynamic modulus ratio E3 / E0 decreased slightly when the SrO cement content was 19% by mass. No. 1 to No. 11 showed a higher dynamic modulus ratio, i.e., a higher heat resistance, than No. 12. Also, for the levels (No. 14 to No. 18) where the SrO cement content was 10% or more by mass and normal alumina cement was used, the dynamic modulus ratio E3 / E0 was higher than No. 12, i.e., a higher heat resistance. In particular, when the amount of SrO cement mixed was 11 mass% or more without the usual alumina cement, the value was more than 15% higher than that of No. 12. In addition, the relationship between the dynamic elastic modulus ratio E3 / E0 was almost consistent with the relationship between the fracture energy.
[0040] As mentioned above, structural spalling occurs due to both slag infiltration and crack generation. Compared to No. 12, a general monolithic refractory, Nos. 1 to 11 and 14 to 18 have less slag infiltration, high hot strength and high hot fracture energy at temperatures above 1000°C, which is the practical range of use, and can be said to be refractories with high structural spalling resistance. It was also confirmed that high hot fracture energy leads to high heat spalling resistance. It was also found that Nos. 3 to 11, which do not contain alumina cement containing calcium aluminate, have better slag wetting resistance. In the levels (No. 14-18) where the SrO cement content was 10% by mass or more and normal alumina cement was used, the same slag infiltration index, hot bending strength, and hot fracture energy were obtained compared to the levels (No. 8-10) where only SrO cement was used and the total amount of SrO cement and normal alumina cement was about the same, and it was found that even when normal alumina cement was added, the structural spalling resistance and slag wettability were excellent. From this, it was found that if the SrO cement content was 10% by mass or more, it was possible to suppress the decline in structural spalling resistance and slag wettability even when normal alumina cement was added.
[0041] Furthermore, it was found that Nos. 4 to 11 and 14 to 18, which contain 7 mass% or more of SrO cement, have superior hot strength at 800°C compared to No. 12, a general monolithic refractory.
[0042] Although the embodiment to which the present invention is applied has been described above, the present invention is not limited by the description that forms part of the disclosure of the present invention according to the present embodiment. In addition, although the description has been given using a general alumina-magnesia monolithic refractory for ladles as an example, since the effect is due to the change in the cement used in the monolithic refractory, all monolithic refractories other than those listed in the above examples are included in the technical scope of the present invention. Furthermore, all other embodiments, examples, operating techniques, etc. made by those skilled in the art based on the present embodiment are included in the technical scope of the present invention. [Industrial Applicability]
[0043] According to the method for using the monolithic refractory of the present invention, when used as a monolithic refractory that comes into contact with high-temperature molten material, it has excellent structural spalling resistance and heat spalling resistance, and is therefore highly durable when used as a container for holding high-temperature molten material. In addition to reducing the unit usage of the refractory, this leads to a reduction in the workload and the respective costs due to a reduction in the frequency of construction. Furthermore, the frequency of demolition is also reduced, which leads to a reduction in the cost of processing the demolition debris and the environmental load. In addition, the reduction in the unit usage of the refractory also reduces the environmental load associated with the production of raw materials. Thus, the present invention is industrially useful because it can enjoy not only economic benefits but also a reduction in the workload and the load on the natural environment.
Claims
1. A method for using an unshaped refractory, which contains 7 mass% or less of alumina cement containing 10 to 40 mass% CaO as calcium aluminate and 2 mass% or more of alumina cement containing 10 to 40 mass% SrO as strontium aluminate in a total amount of 7 mass% or more and less than 20 mass%, in a refractory raw material, is used in an environment in which it comes into contact with a molten material at 1000°C or more.
2. A method for using the unshaped refractory material according to claim 1, comprising using an unshaped refractory material containing 10 mass% or more of alumina cement containing 10 to 40 mass% of SrO as strontium aluminate.
3. A method for using an unshaped refractory, which does not contain alumina cement containing calcium aluminate in the refractory raw materials, but contains alumina cement containing 10 to 40 mass% SrO as strontium aluminate in an amount of 5 mass% or more and less than 20 mass%, is used in an environment in which it comes into contact with a molten material at 1000°C or more.
4. A method for using an unshaped refractory, which is prepared by blending 7 mass% or less of alumina cement containing 10 to 40 mass% CaO as calcium aluminate and 7 mass% or more of alumina cement containing 10 to 40 mass% SrO as strontium aluminate in a total amount of 7 mass% or more and less than 20 mass% in refractory raw materials, is used in an environment in which the unshaped refractory is in contact with a molten material at 800°C or more.
5. A method for using the unshaped refractory material according to claim 4, comprising using an unshaped refractory material containing 10 mass% or more of alumina cement containing 10 to 40 mass% of SrO as strontium aluminate.
6. A method for using the unshaped refractory material according to any one of claims 1 to 5, wherein the temperature of the melt is 1200°C or higher.
7. A method for using the unshaped refractory material according to any one of claims 1 to 5, wherein the temperature of the melt is 1400°C or higher.
8. A method for using the unshaped refractory material according to any one of claims 1 to 5, wherein the refractory raw materials other than cement are mainly composed of alumina and contain magnesia.
9. the melt comprises molten iron or steel, A method for using the unshaped refractory material according to claim 8, comprising applying the unshaped refractory material to a steelmaking vessel.
Citation Information
Patent Citations
Binder for monolithic refractory, and monolithic refractory
JP2010120843A
Monolithic refractory
JP2017066025A
Monolithic refractory
JP2022026926A
Castable refractory and molten steel ladle using the same
JP2022065401A
Castable refractory and molten steel ladle
JP2022161032A